2023
DOI: 10.1126/sciadv.ade0293
|View full text |Cite
|
Sign up to set email alerts
|

Secreted endogenous macrosomes reduce Aβ burden and ameliorate Alzheimer’s disease

Cunli Wang,
Yiming Yang,
Xiaoyu Zhang
et al.

Abstract: Innovative therapeutic strategies are urgently needed for Alzheimer’s disease (AD) due to the increasing size of the aging population and the lack of effective drug treatment. Here, we report the therapeutic effects of extracellular vesicles (EVs) secreted by microglia, including macrosomes and small EVs, on AD-associated pathology. Macrosomes strongly inhibited β-amyloid (Aβ) aggregation and rescued cells from Aβ misfolding–induced cytotoxicity. Furthermore, macrosome administration reduced Aβ plaques and ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…1 H-1 H nuclear magnetic resonance (NMR) spectra provided the details of binding between CP-1 and DG12. 52,53 First, the chemical shi attribution of each H proton in CP-1 and DG12 was assigned according to the two-dimensional 1 H-1 H (correlation spectroscopy) COSY and 13 C-1 H (heteronuclear singular quantum correlation) HSQC NMR spectra (Fig. S21-S25 in the ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…1 H-1 H nuclear magnetic resonance (NMR) spectra provided the details of binding between CP-1 and DG12. 52,53 First, the chemical shi attribution of each H proton in CP-1 and DG12 was assigned according to the two-dimensional 1 H-1 H (correlation spectroscopy) COSY and 13 C-1 H (heteronuclear singular quantum correlation) HSQC NMR spectra (Fig. S21-S25 in the ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…There is mounting experimental evidence indicating size-dependent beneficial effects of different EV subpopulation. While in some reports beneficial effects of small EVs have been shown 11,12 , others indicated the superior beneficial effects of large EVs for alleviating molecular phenotypes of AD 13 . These observations were attributed to the size and size distribution of EV subpopulation, ultimately effecting their cargo contents and their therapeutic properties 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, therapeutic MSCs-derived exosomes have been shown to exhibit neuroprotective effects by regulating pathways associated with oxidative stress, neuroinflammation, apoptosis, reduced NFT and Amyloid plaques on cell and animal models of AD 11,12 . Interestingly, large EVs have been shown to reduce pathological changes and restore homeostasis in a mouse model of AD more effectively 13 . In addition, previous studies have highlighted that EVs isolated by different methods yield different size distribution and dependent on the size EVs carry distinct cargo that affects their features 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed that microglial macrosomes reduce the amyloid burden and ameliorate AD, but microsomes have completely opposite effects. [ 48 ] It is important to note whether the original cell membranes or EVs are damaged during preparation. Furthermore, the long‐term safety and potential immunogenicity of these nanomaterials must be thoroughly evaluated.…”
Section: Discussionmentioning
confidence: 99%